2022
DOI: 10.2174/2210327911666210126123257
|View full text |Cite
|
Sign up to set email alerts
|

Flexible, Piezoelectric Aluminum-Doped Zinc Oxide Energy Harvesters with Printed Electrodes for Wearable Applications

Abstract: Aims: Recent advancements in sensing technology and wireless communications have accelerated the development of the Internet of Things (IoT) which promote the usage of wearable sensors. An emerging trend is to develop self-sustainable wearable devices, thus eliminating the necessity of the user to carry bulky batteries. In this work, the development of a flexible piezoelectric energy harvester that is capable of harvesting energy from low frequency vibrations is presented. The target application of this energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 118 publications
0
1
0
Order By: Relevance
“…Another study reported the use of zinc oxide dope aluminum-based energy harvester as a cantilever structure. The effect of ZnO showed large output voltages with small displacements and was able to generate a 0.867 V rms output voltage [50]. This trend, however, cannot be observed in KNN and ZnO piezoelectric materials [50][51][52], therefore, KNN and ZnO seem more suitable for use in smaller devices.…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported the use of zinc oxide dope aluminum-based energy harvester as a cantilever structure. The effect of ZnO showed large output voltages with small displacements and was able to generate a 0.867 V rms output voltage [50]. This trend, however, cannot be observed in KNN and ZnO piezoelectric materials [50][51][52], therefore, KNN and ZnO seem more suitable for use in smaller devices.…”
Section: Introductionmentioning
confidence: 99%